2004
DOI: 10.1128/jcm.42.11.5001-5006.2004
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mycobacterial Interspersed Repetitive Unit Typing to Manitoba Tuberculosis Cases: Can Restriction Fragment Length Polymorphism Be Forgotten?

Abstract: Since 1993, all Mycobacterium tuberculosis isolates recovered in the province of Manitoba, Canada, have been genotyped by the standard IS6110-restriction fragment length polymorphism (RFLP) method for routine surveillance, prevention, and control purposes. To date, our laboratory has collected 1,290 isolates, from which we have identified approximately 390 unique fingerprint patterns or "types." Although the standard method is well known for being a lengthy and labor-intensive procedure, a more efficient alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 30 publications
1
28
0
1
Order By: Relevance
“…MIRU-VNTR genotyping has been reported to identify as many clustered cases as RFLP genotyping (27), which led MIRU-VNTR-based genotyping to be chosen for the epidemiological survey in different institutions (5,8). However, in our study, MIRU-VNTR genotyping clustered isolates in a higher proportion than did RFLP genotyping.…”
Section: Discussionmentioning
confidence: 56%
“…MIRU-VNTR genotyping has been reported to identify as many clustered cases as RFLP genotyping (27), which led MIRU-VNTR-based genotyping to be chosen for the epidemiological survey in different institutions (5,8). However, in our study, MIRU-VNTR genotyping clustered isolates in a higher proportion than did RFLP genotyping.…”
Section: Discussionmentioning
confidence: 56%
“…MIRU-VNTR genotyping based on a 12-loci set (MIRU-12) has been evaluated in several studies in different settings. Some authors have found it to show a discriminatory power equivalent to that of RFLP and have considered it an alternative to IS6110-RFLP for epidemiological purposes [4][5][6][7] . However, other authors have found limitations in its discriminatory power and incomplete correlation with the RFLP analysis [8][9][10] , indicating that MIRU analysis should be combined with an additional genotyping method [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Among the different described sets of MIRU-VNTR loci (8,10,14,17,20,22,27), a system based on 12 loci (15,25,27), is now the most widely used in clinical mycobacteriology (see, for example, reference 1) and for local outbreak investigation (11). Genotypes based on these 12 loci are highly stable among epidemiologically linked isolates but sufficiently diverse to generate a resolution approaching that of IS6110-RFLP in some sets of isolates from low-incidence settings or from diverse geographic origins (2,15,25).…”
mentioning
confidence: 99%